A peritoneal dialysis bag infusion membrane material and a preparation method thereof
Patent Information
- Application Number
- CN202511018855.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-07-23
AI Technical Summary
而现有非PVC腹膜透析袋输液膜材料在环保性能及阻隔性能等方面有待进一步提高
[0027] Preferably, the secondary curing time is 1.5h-2.5h.
Smart Images

Figure CN120699390B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of infusion materials technology, and specifically discloses an infusion membrane material for peritoneal dialysis bags and its preparation method. Background Technology
[0002] Polyvinyl chloride, or PVC for short, is a thermoplastic resin polymerized from vinyl chloride under the action of an initiator. While PVC possesses advantages such as excellent physical and mechanical properties, low price, and simple production processes, plasticizers like DEHP and stabilizers containing various heavy metal ions must be added during production to improve its plasticity, flexibility, stability, flowability during processing, mold release, and surface smoothness. Recent studies have shown that the addition of these non-degradable toxic substances to PVC materials to stabilize and soften them has adverse effects on the environment and human health.
[0003] Peritoneal dialysis, as a crucial alternative treatment for end-stage renal disease, is highly dependent on the packaging of the peritoneal dialysis solution for its therapeutic effect. The infusion membrane of the peritoneal dialysis bag, as a key material for packaging the dialysis solution, significantly impacts the quality and safety of the solution, as well as the patient's treatment experience. Due to the risks associated with plasticizers, poor thermal stability, and insufficient barrier properties, PVC membranes are gradually being replaced by non-PVC materials. However, existing non-PVC peritoneal dialysis bag infusion membrane materials require further improvement in terms of environmental performance and barrier properties. Summary of the Invention
[0004] To address the shortcomings of existing peritoneal dialysis bag infusion membrane materials in terms of environmental performance and barrier properties, this invention introduces bio-based resin materials, ethylene-vinyl acetate copolymer and other bio-based polymer materials, as well as nano-montmorillonite into the peritoneal dialysis bag infusion membrane material, thereby improving the product's environmental friendliness and barrier properties against gases such as water vapor and oxygen.
[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a peritoneal dialysis bag infusion membrane material, comprising the following components in parts by weight: 25-35 parts of a bio-based resin composition, 25-35 parts of an epoxy resin, 10-15 parts of a polyacrylate, 35-40 parts of a monomer composition, 2.5-4 parts of an initiator, 1.5-2.5 parts of a crosslinking agent, 5-7 parts of a curing agent, 4-6 parts of nano-montmorillonite, and 2.5-3.5 parts of an environmentally friendly plasticizer; The bio-based resin composition includes polylactic acid-glycolic acid copolymer, ethylene-vinyl acetate copolymer, and maleic anhydride-modified ethylene-vinyl acetate copolymer.
[0006] The D of the nano-montmorillonite 90 ≤200nm.
[0007] This invention introduces a ternary bio-based resin composed of polylactic acid-glycolic acid copolymer (PLGA), ethylene-vinyl acetate copolymer (EVA), and maleic anhydride-modified ethylene-vinyl acetate copolymer (EVA-G-MAH), along with nano-montmorillonite, to systematically improve the environmental performance and barrier properties of peritoneal dialysis bag infusion membrane materials while ensuring mechanical strength.
[0008] In this ternary bio-based resin composite system, PLGA, as a biodegradable polymer, can be degraded by microorganisms after disposal, replacing part of the traditional petroleum-based resin and reducing the risk of white pollution at the source. EVA has excellent biocompatibility and good compatibility with PLGA, improving the flexibility of the membrane material, increasing the elongation at break, and reducing the system's dependence on phthalate plasticizers. EVA-G-MAH, as an interfacial compatibilizer, enhances the interphase bonding force and improves the tensile strength of the system through the reaction of the anhydride groups with the hydroxyl / carboxyl groups of PLGA. By rationally blending PLGA, EVA, EVA-G-MAH, and epoxy resin, a "bio-based-traditional resin" composite system is formed, which replaces part of the fossil-based materials while ensuring mechanical strength, making it more environmentally friendly.
[0009] The ester groups of PLGA, the vinyl acetate groups of EVA, and the carboxyl groups in EVA-G-MAH can form hydrogen bonds or covalent bonds (COC) with the hydroxyl groups on the surface of montmorillonite, preventing the formation of defective pores and enhancing the thickness of the interfacial layer and the interfacial bonding strength. Stress is effectively transferred through interfacial hydrogen and covalent bonds, and the rigid network formed by the nano-montmorillonite sheets and PLGA improves the mechanical properties of the membrane material. Furthermore, the nanoscale sheet structure of nano-montmorillonite can be randomly dispersed or oriented in the membrane material, significantly extending the permeation path of oxygen and water vapor.
[0010] Preferably, the mass ratio of the polylactic acid-glycolic acid copolymer, the ethylene-vinyl acetate copolymer, and the maleic anhydride-modified ethylene-vinyl acetate copolymer is 1.8-2.2:0.9-1.1:0.4-0.6.
[0011] Preferably, the monomer composition includes butyl acrylate, isooctyl acrylate, methyl methacrylate, and styrene.
[0012] The quaternary monomers in the monomer composition have a synergistic effect. Butyl acrylate, as a flexible monomer, provides elastic segments to improve the flexibility of the film; isooctyl acrylate, as an ultra-flexible monomer, further enhances the flowability of the molecular chain and synergistically forms a "soft-soft" structure with butyl acrylate, improving bending resistance; methyl methacrylate, as a rigid monomer, enhances cohesion through polar ester groups, improving hardness and tensile strength; styrene contains benzene rings, which can improve immersion stability and form π-π stacking with epoxy resin, enhancing interfacial bonding.
[0013] More preferably, the mass ratio of butyl acrylate, isooctyl acrylate, methyl methacrylate and styrene is 1:1.7-2.2:0.8-1.0:1.4-1.6.
[0014] In this invention, the preferred mass ratio of the four monomers is as follows: the mass ratio of butyl acrylate to isooctyl acrylate is controlled at 1:1.7-2.2 to ensure that the flexible segments dominate, forming a continuous phase structure while avoiding excessive stickiness. The mass ratio of methyl methacrylate to styrene is controlled at 0.8-1.0:1.4-1.6, with styrene slightly exceeding methyl methacrylate, to balance hardness and brittleness. The total mass ratio of soft / hard monomers is approximately 3:2, constructing a bicontinuous phase structure with flexible support and rigid protection.
[0015] Preferably, the initiator comprises dicumyl peroxide.
[0016] Preferably, the crosslinking agent comprises pentaerythritol tetraacrylate.
[0017] Preferably, the curing agent comprises cashew phenol modified amine.
[0018] For example, in this invention, cashew phenol modified phenolic amine is selected, with a viscosity of 20,000~50,000 cps at 25°C and an amine value of 270±30 mg KOH / g; The preferred curing agent of this invention, cashew phenol modified amine, not only has the advantages of low toxicity, environmental friendliness, and low-temperature curing, but also improves the toughness and water resistance of epoxy resin network while ensuring safety.
[0019] Preferably, the environmentally friendly plasticizer includes tributyl citrate.
[0020] Tributyl citrate is non-toxic. In its molecular structure, three ester groups form hydrogen bonds with the polymer chain, resulting in low migration in dialysis solution at 37°C. Furthermore, the solubility parameters of tributyl citrate are similar to those of PLGA and EVA, indicating good compatibility and improved plasticizing efficiency.
[0021] Secondly, the present invention provides a method for preparing the above-mentioned peritoneal dialysis bag infusion membrane material, the preparation method comprising the following steps: S1. According to the preset ratio, the bio-based resin composition, epoxy resin, polyacrylate, monomer composition and environmentally friendly plasticizer are mixed evenly, and an initiator is added under an inert gas atmosphere. The prepolymerization reaction is carried out at 78℃-82℃, and then a secondary polymerization reaction is carried out at 110℃-115℃. S2. After the secondary polymerization reaction is completed, a crosslinking agent is added to the reaction system, and a crosslinking reaction is carried out at 115℃-120℃; S3. After the crosslinking reaction is completed, nano-montmorillonite is added to the reaction system, mixed well, and then a curing agent is added. After a first curing at 122℃-128℃, a second curing is carried out at 130℃-140℃ to obtain the peritoneal dialysis bag infusion membrane material.
[0022] This invention improves the chemical resistance, oxygen permeability, and water vapor permeability of the product by controlling the monomer polymerization reaction through gradient temperature rise and gradient curing process. In step S1, the monomer polymerization is controlled by gradient temperature rise. During the pre-polymerization stage, highly reactive monomers are preferentially initiated to form a soft segment core. This setting avoids compositional inhomogeneity caused by differences in monomer reactivity ratios. Then, the temperature is raised to 110℃-115℃ to initiate the formation of a hard segment shell from styrene and methyl methacrylate. Through core-shell structure regulation (soft segment: hard segment = 3:2), the glass transition temperature of the copolymer is gradient-distributed. This step, through "soft core-hard shell" gradient polymerization, enables the copolymer to form an interpenetrating network structure, reducing the fluctuation range of elongation at break and meeting the dual requirements of dialysis bags for bending resistance and puncture resistance. In step S3, during the first curing, the cashew phenol-modified amine curing agent undergoes initial cross-linking with the epoxy resin to form a three-dimensional network skeleton. This temperature range avoids overheating of the PLGA while ensuring the initiation of the curing reaction. During the secondary curing process, the temperature is raised to the optimal reaction temperature of the curing agent, which promotes the complete reaction of the remaining amine groups. At the same time, this stage promotes the further exfoliation of montmorillonite layers, which are oriented and arranged under the action of melt flow, reducing oxygen permeability and water vapor permeability.
[0023] Preferably, the prepolymerization reaction takes 15-25 minutes.
[0024] The secondary polymerization reaction takes 35-45 minutes.
[0025] Preferably, the crosslinking reaction takes 1-2 hours.
[0026] Preferably, the curing time for the first curing cycle is 0.8h-1.2h.
[0027] Preferably, the secondary curing time is 1.5h-2.5h.
[0028] The method for preparing peritoneal dialysis bag infusion membrane material provided by this invention has advantages such as high production efficiency, strong equipment compatibility, and small performance fluctuations between product batches. It provides technical support for the large-scale production of high-performance peritoneal dialysis bag membrane material, and is especially suitable for clinical scenarios with high requirements for material stability and biocompatibility. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 The tensile strength test results of different peritoneal dialysis bag infusion membranes in the effect examples of this invention; Figure 2 The results of water vapor permeation measurement of different peritoneal dialysis bag infusion membranes in the example of the effectiveness of this invention; Figure 3 The results of nitrogen and oxygen permeation measurements of different peritoneal dialysis bag infusion membranes in the example of the present invention. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0032] To better illustrate the embodiments provided by the present invention, further examples are given below.
[0033] The cashew phenol-modified phenolic amine used in this embodiment of the invention was purchased from Shanghai Zhipu Chemical Co., Ltd. Polylactic acid-glycolic acid copolymer was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd. The ethylene-vinyl acetate copolymer was purchased from Hanwha Group; The maleic anhydride-modified ethylene-vinyl acetate copolymer was purchased from Dongguan Mingyuan Plastics Co., Ltd.
[0034] Example 1 This embodiment provides a peritoneal dialysis bag infusion membrane material, comprising the following components in parts by weight: The composition consists of 35 parts of a bio-based resin composition, 30 parts of an epoxy resin, 12 parts of a polyacrylate, 37.4 parts of a monomer composition, 3 parts of dicumyl peroxide, 2 parts of pentaerythritol tetraacrylate, 6 parts of cashew phenol-modified phenolic amine, 5 parts of nano-montmorillonite, and 3 parts of tributyl citrate. The bio-based resin composition specifically includes: 20 parts of polylactic acid-glycolic acid copolymer, 10 parts of ethylene-vinyl acetate copolymer, and 5 parts of maleic anhydride-modified ethylene-vinyl acetate copolymer. The monomer composition specifically includes: 7 parts butyl acrylate, 14 parts isooctyl acrylate, 6 parts methyl methacrylate, and 10.4 parts styrene; D of nano-montmorillonite 90 ≤200nm.
[0035] The preparation method of the above-mentioned peritoneal dialysis bag infusion membrane material specifically includes the following steps: S1. According to the preset ratio, the bio-based resin composition, epoxy resin, polyacrylate, monomer composition and tributyl citrate are mixed evenly, and dicumyl peroxide is added under nitrogen atmosphere. The prepolymerization reaction is carried out at 80°C for 20 min, and then the secondary polymerization reaction is carried out at 115°C for 40 min. S2. After the secondary polymerization reaction is completed, pentaerythritol tetraacrylate is added to the reaction system, and a crosslinking reaction is carried out at 120°C for 1 hour; S3. After the crosslinking reaction is completed, nano-montmorillonite is added to the reaction system, mixed well, and then cashew phenol-modified phenolic amine is added. After a first curing at 125°C, a second curing at 135°C is performed to obtain the peritoneal dialysis bag infusion membrane material, which is denoted as peritoneal dialysis bag infusion membrane material I. The curing time for the first stage is 1 hour; the curing time for the second stage is 2 hours.
[0036] Example 2 This embodiment provides a peritoneal dialysis bag infusion membrane material, comprising the following components in parts by weight: The composition comprises 25 parts of bio-based resin, 25 parts of epoxy resin, 10 parts of polyacrylate, 35 parts of monomer composition, 2.5 parts of dicumyl peroxide, 1.5 parts of pentaerythritol tetraacrylate, 5 parts of cashew phenol-modified phenolic amine, 4 parts of nano-montmorillonite, and 2.5 parts of tributyl citrate. The bio-based resin composition specifically includes: 13 parts of polylactic acid-glycolic acid copolymer, 7.8 parts of ethylene-vinyl acetate copolymer, and 4.2 parts of maleic anhydride-modified ethylene-vinyl acetate copolymer; The monomer composition specifically includes: 7.1 parts butyl acrylate, 12.2 parts isooctyl acrylate, 5.7 parts methyl methacrylate, and 10 parts styrene; D of nano-montmorillonite 90 ≤200nm.
[0037] The preparation method of the above-mentioned peritoneal dialysis bag infusion membrane material specifically includes the following steps: S1. According to the preset ratio, the bio-based resin composition, epoxy resin, polyacrylate, monomer composition and tributyl citrate are mixed evenly, and dicumyl peroxide is added under nitrogen atmosphere. The prepolymerization reaction is carried out at 78°C for 25 min, and then the secondary polymerization reaction is carried out at 110°C for 45 min. S2. After the secondary polymerization reaction is completed, pentaerythritol tetraacrylate is added to the reaction system, and a crosslinking reaction is carried out at 115°C for 2 hours. S3. After the cross-linking reaction is completed, nano-montmorillonite is added to the reaction system, mixed well, and then cashew phenol-modified phenolic amine is added. After a first curing at 122°C, a second curing at 130°C is performed to obtain the peritoneal dialysis bag infusion membrane material, which is denoted as peritoneal dialysis bag infusion membrane material II. The curing time for the first stage is 1.2 hours; the curing time for the second stage is 2.5 hours.
[0038] Example 3 This embodiment provides a peritoneal dialysis bag infusion membrane material, comprising the following components in parts by weight: The composition comprises 30 parts of a bio-based resin composition, 35 parts of an epoxy resin, 15 parts of a polyacrylate, 40 parts of a monomer composition, 4 parts of dicumyl peroxide, 2.5 parts of pentaerythritol tetraacrylate, 7 parts of cashew phenol-modified phenolic amine, 6 parts of nano-montmorillonite, and 3.5 parts of tributyl citrate. The bio-based resin composition specifically includes: 19 parts of polylactic acid-glycolic acid copolymer, 7.5 parts of ethylene-vinyl acetate copolymer, and 3.5 parts of maleic anhydride-modified ethylene-vinyl acetate copolymer; The monomer composition specifically includes: 7 parts butyl acrylate, 15 parts isooctyl acrylate, 7 parts methyl methacrylate, and 11 parts styrene; D of nano-montmorillonite 90 ≤200nm.
[0039] The preparation method of the above-mentioned peritoneal dialysis bag infusion membrane material specifically includes the following steps: S1. According to the preset ratio, the bio-based resin composition, epoxy resin, polyacrylate, monomer composition and tributyl citrate are mixed evenly, and dicumyl peroxide is added under nitrogen atmosphere. The prepolymerization reaction is carried out at 82°C for 15 min, and then the secondary polymerization reaction is carried out at 115°C for 35 min. S2. After the secondary polymerization reaction is completed, pentaerythritol tetraacrylate is added to the reaction system, and a crosslinking reaction is carried out at 118°C for 1.5 h; S3. After the crosslinking reaction is completed, nano-montmorillonite is added to the reaction system, mixed well, and then cashew phenol-modified phenolic amine is added. After a first curing at 128°C, a second curing at 140°C is performed to obtain the peritoneal dialysis bag infusion membrane material, which is referred to as peritoneal dialysis bag infusion membrane material III. The curing time for the first stage is 0.8 hours, and the curing time for the second stage is 1.5 hours.
[0040] Comparative Example 1 This comparative example provides a peritoneal dialysis bag infusion membrane material. The raw materials, dosages, and preparation methods of this peritoneal dialysis bag infusion membrane material are basically the same as those in Example 1. The only difference is that nano-montmorillonite is not added, and the composition of the other raw materials and the preparation process parameters are not changed. The peritoneal dialysis bag infusion membrane material obtained is referred to as peritoneal dialysis bag infusion membrane material comparison I.
[0041] Comparative Example 2 This comparative example provides a peritoneal dialysis bag infusion membrane material. The raw materials, dosages, and preparation methods of this peritoneal dialysis bag infusion membrane material are basically the same as those in Example 1. The only difference is that maleic anhydride-modified ethylene-vinyl acetate copolymer is not added, and the composition of the remaining raw materials and the preparation process parameters are not changed. The peritoneal dialysis bag infusion membrane material obtained is referred to as peritoneal dialysis bag infusion membrane material II.
[0042] Example of effect In the clean area, the peritoneal dialysis bag infusion membrane material from Examples 1-3 and Comparative Examples 1-2 was used as the middle layer material. The peritoneal dialysis bag infusion membrane was prepared by multi-layer co-extrusion technology using the method described in Chinese Patent CN201410117422.7, and was accordingly referred to as peritoneal dialysis infusion membrane I~III and peritoneal dialysis infusion membrane pair I~pair II.
[0043] The inner layer material is composed of 70% polypropylene (PP) and 30 wt% styrene-ethylene-butene rubber-styrene copolymer (SEBS); the outer layer material is composed of 80% polypropylene (PP) and 20 wt% styrene-ethylene-butene rubber-styrene copolymer (SEBS). The total thickness of the infusion membrane in this invention is 240 μm, with the inner and outer layers each having a thickness of 85 μm and the middle layer having a thickness of 70 μm.
[0044] 1. Appearance Under bright natural light, visually inspect the peritoneal dialysis bag. It should be transparent, smooth, and free of any visible foreign matter. Testing has shown that the appearance of the infusion membrane in the peritoneal dialysis bag provided by this invention meets all requirements.
[0045] 2. Tensile strength evaluation This invention uses YBB00112003-2015 to determine the tensile strength of infusion membranes in different peritoneal dialysis bags. The results of the tensile strength tests for the infusion membranes of different peritoneal dialysis bags are as follows: Figure 1 As shown.
[0046] 3. Evaluation of barrier effect Water vapor permeability was determined according to method YBB00092003, and nitrogen and oxygen permeability were determined according to method YBB00082003. The results of water vapor permeability measurements for different peritoneal dialysis bag infusion membranes are as follows: Figure 2 As shown, the results of nitrogen and oxygen permeation measurements for different peritoneal dialysis bag infusion membranes are as follows: Figure 3 As shown.
[0047] Depend on Figure 1-3 It can be seen that the peritoneal dialysis infusion membrane prepared using the peritoneal dialysis bag infusion membrane material provided in the embodiments of the present invention has a tensile strength of 35.8N-38.9N and a water vapor permeability of 0.51-0.65g / (m³). 2 • 24h), nitrogen permeation rate is 8.4-11.4 g / (m³). 2 • 24h), oxygen permeability is 60.9-73.8 g / (m³). 2 •24h), with superior overall performance. Specifically, compared to peritoneal dialysis infusion membrane pair I, peritoneal dialysis infusion membranes I-III and II show significantly reduced water vapor transmission, nitrogen transmission, and oxygen transmission, while mechanical properties are significantly improved. Compared to peritoneal dialysis infusion membrane pair II, peritoneal dialysis infusion membranes I-III show significantly reduced nitrogen and oxygen transmission, while tensile strength is slightly increased and water vapor transmission is slightly reduced.
[0048] Because nano-montmorillonite was added in Examples 1-3 and Comparative Example 2, its layered structure may form a "zigzag path effect" in the polymer matrix, significantly extending the diffusion path of gases and water vapor, thereby improving barrier properties. Secondly, the interfacial interaction between nano-montmorillonite and the polymer matrix can further reduce molecular permeability. Furthermore, the interfacial bonding between nano-montmorillonite and the matrix may enhance the mechanical properties of the material, increasing strength by bearing loads and inhibiting crack propagation. In Comparative Example 1, the absence of nano-montmorillonite in the preparation of the peritoneal dialysis bag infusion membrane material resulted in reduced mechanical properties and gas barrier performance.
[0049] In Examples 1-3, maleic anhydride-modified ethylene-vinyl acetate copolymer was added during the preparation of the peritoneal dialysis bag infusion membrane material. This polymer can form hydrogen bonds or chemical reactions with polar components such as epoxy resin and PLGA in the system, improving interfacial compatibility, reducing phase separation, and making the barrier layer more uniform and dense, thus indirectly improving barrier performance. Furthermore, because the maleic anhydride-modified ethylene-vinyl acetate copolymer can improve interfacial bonding, the load transfer is more uniform when the material is under stress, reducing stress concentration. In Comparative Example 2, the absence of maleic anhydride-modified ethylene-vinyl acetate copolymer in the preparation of the peritoneal dialysis bag infusion membrane material may lead to a decrease in barrier performance and mechanical strength.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A peritoneal dialysis bag infusion membrane material, characterized in that, The product comprises the following components in parts by weight: 25-35 parts of bio-based resin composition, 25-35 parts of epoxy resin, 10-15 parts of polyacrylate, 35-40 parts of monomer composition, 2.5-4 parts of initiator, 1.5-2.5 parts of crosslinking agent, 5-7 parts of curing agent, 4-6 parts of nano-montmorillonite, and 2.5-3.5 parts of environmentally friendly plasticizer; The bio-based resin composition comprises polylactic acid-glycolic acid copolymer, ethylene-vinyl acetate copolymer, and maleic anhydride-modified ethylene-vinyl acetate copolymer in a mass ratio of 1.8-2.2:0.9-1.1:0.4-0.
6. The monomer composition comprises butyl acrylate, isooctyl acrylate, methyl methacrylate and styrene in a mass ratio of 1:1.7-2.2:0.8-1.0:1.4-1.6; The initiator includes dicumyl peroxide; The crosslinking agent includes pentaerythritol tetraacrylate; The curing agent includes cashew phenol modified amine curing agent.
2. The peritoneal dialysis bag infusion membrane material as described in claim 1, characterized in that, The environmentally friendly plasticizer includes tributyl citrate.
3. The method for preparing the peritoneal dialysis bag infusion membrane material as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: S1. According to the preset ratio, the bio-based resin composition, epoxy resin, polyacrylate, monomer composition and environmentally friendly plasticizer are mixed evenly, and an initiator is added under an inert gas atmosphere. The prepolymerization reaction is carried out at 78℃-82℃, and then a secondary polymerization reaction is carried out at 110℃-115℃. S2. After the secondary polymerization reaction is completed, a crosslinking agent is added to the reaction system, and a crosslinking reaction is carried out at 115℃-120℃; S3. After the crosslinking reaction is completed, nano-montmorillonite is added to the reaction system, mixed well, and then a curing agent is added. After a first curing at 122℃-128℃, a second curing is carried out at 130℃-140℃ to obtain the peritoneal dialysis bag infusion membrane material.
4. The method for preparing the peritoneal dialysis bag infusion membrane material as described in claim 3, characterized in that, The prepolymerization reaction time is 15 min-25 min; and / or The secondary polymerization reaction takes 35-45 minutes.
5. The method for preparing the peritoneal dialysis bag infusion membrane material as described in claim 3, characterized in that, The cross-linking reaction takes 1-2 hours.
6. The method for preparing the peritoneal dialysis bag infusion membrane material as described in claim 3, characterized in that, The curing time for the first stage is 0.8h-1.2h; and / or The secondary curing time is 1.5h-2.5h.
Citation Information
Patent Citations
A kind of raw material blending polypropylene multi-layer co-extrusion transfusion film and its production method
CN103879101B
Poly(lactic-co-glycolic acid) / polyhydroxyalkanoate membrane for dialysis and preparation method thereof
CN104226125A
Non-PVC (Polyvinyl Chloride) peritoneal dialysis bag transfusion film material and preparation method thereof
CN107189022A